Corporate Social Responsibility (CSR), Firm Size, Profitability, and Leverage On Earnings Response Coefficient (ERC) (An Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange for the period of 2015- 2018) - Sasongko, Noer; Puspawati, Ragil Kuning; Wijayanto, Kusuma (Riset Akuntansi dan Keuangan Indonesia, 2020)
This study aims to examine the effect of corporate social responsibility (CSR), firm size, profitability, and leverage on the earnings response coefficient (ERC). The type of this research was quantitative. The type of data used was secondary data obtained from www.idx.co.id. The population involved in this study was the manufacturing companies that were listed on the Indonesia Stock Exchange during the 2015-2018 period. Whereas, this research sample was determined by purposive sampling method in accordance with predetermined criteria. The analytical method employed was multiple linear regression analysis. The results of this study indicated that variables that had an effect on the earnings response coefficient were corporate social responsibility and firm size, while profitability and leverage had no impact on the earnings response coefficient.